(untitled) (PUSA Journal of Hospitality and Applied Sciences, 2016)
Background: Fairs and festivals are important part of life. It contributes peace and imparts relaxation, pleasure to human being. In India we observe number of festivals throughout the year. Odisha is known for its festivals and folk cultures. In Odisha different fairs and festivals attract culture tourists and promote tourism in the state. Objective: The objective of the study is to identify the important attributes to attract tourists at GopalPur beach festival of Odisha. Methodology: The study was conducted by taking 100 tourists as the sample size. The survey questionnaires were administered along with face to face interviews with the tourists or the respondents. A 5-Point Likert scale was used to measure tourist’s satisfaction. Results: The findings of this research revealed that attributes like Art and Craft, Sand Art, Local community etc. had contributed in the development of GopalPur Beach festival of Odisha. Conclusion : Cultural tourism can thus help in the economic and social development of the state.